Positron Emission Tomography (PET) in Clinical Medicine and Bangladesh Perspective - Majumder, MSH (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Positron emission tomography (PET) imaging devices were first developed in the 1970. In the last thirty years PET imaging has been extensively used in research, but only in the last few years the technology has become more widely available for clinical applications. Most of the early works with PET focused on brain metabolism, partly because of the smaller size of detector needed to study head. With the introduction of improved instruments and suitable radionuclide, applications in oncology have developed into the major clinical uses of PET. Myocardial viability is usually assessed using perfusion studies with Signal photon emission computed tomography (SPECT) but in case of inconclusive result, metabolic assessment with short-lived PET tracers may be more decisive. PET allows study of body function; it helps detection of alterations in biochemical processes that suggest disease before changes in anatomy are apparent with other imaging tests, such as computed tomography (CT) or magnetic resonance imaging (MRI). The future of PET imaging is bright. New geometries are being studied especially to develop organ specific imaging devices, new detector materials are being developed and techniques for reconstruction are improving. However, perhaps the most important need for further utilization of PET imaging is the development of new radiopharmaceuticals or radiotracer compounds and better understanding of cellular physiology and metabolism in disease states. Until recently, Bangladesh had no positron emission tomography scanner, though the neighboring countries like India, Pakistan, Thailand & Singapore have PET scanning for last several years. PET scanning in Bangladesh has been introduced by a multidisciplinary tertiary level private hospital – United Hospital, Gulshan, Dhaka recently. Key Words: Position emission tomography; Positron 18; Flurodeoxyglucose DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9436 JBCPS 2011; 29(3): 151-157